The Fungsi-Fungsi yang Membentuk Framework dari Corporate University - Ade Priaman S. Munajat (IPB University, 2021)
Implementation of a Corporate University in various organizations was truly able to realize organizational expectations in achieving organizational goals and objectives. Corporate University, which is part of an organizational learning process, is believed to assist organizations to move agile, be able to adapt, be responsive, and ready to face changes that continue to occur in times of uncertainty or known as VUCA. The functions chosen by an organization informing the Framework of the Corporate University can vary and change so that in the end a Framework from the Corporate University can be formed which is proven to have a positive impact in realizing the goals and objectives of the organization over a long period of time and requires considerable costs. For organizations that are just about to implement a Corporate University, it is crucial to be able to identify effective and efficient functions in the process of forming a Framework from a Corporate University that is suitable for their organization. This research was conducted using a qualitative descriptive research method approach to reveal the respective functions that make up the Corporate University framework to provide understanding and consideration for any organization that is new to implementing Corporate University. Sources of data in this study were obtained from the results of benchmarking with institutions or organizations that are considered established in the application of the Corporate University and literature studies from books, journals, and related laws and regulations.